Hermeneutics and Technology: Poetry Translation with CAT Tool - Lolan, Pilomena Bana; Hartati, Elysa (Kompetensi : Jurnal Pendidikan dan Humaniora Fakultas Keguruan dan Ilmu Pendidikan UNIBA, 2024)
This research explored the relationship between hermeneutics and technology in poetry translation using the Computer-Assisted Translation (CAT) Tool, specifically Matecat. This research employed a case study with Ricoeur’s hermeneutic analysis model, which consisted of three stages: wager, verification, and transformation. The findings indicated that while Matecat facilitated the translation, human intervention remained essential in preserving meaning and aesthetic aspects of poetry by choosing the appropriate words in the target language. The human involvement to make the poetry translation accurate, acceptable, and readable was necessary. This research concluded that technology itself could not fully replace human translators in literary translation, especially poetry. Thus, future research should explore other CAT Tools and their effectiveness in translating literary texts.